2009
DOI: 10.3184/030823409x465394
|View full text |Cite
|
Sign up to set email alerts
|

Raney Ni-Al alloy mediated hydrodehalogenation and aromatic ring hydrogenation of halogenated phenols in aqueous medium

Abstract: Raney Ni-Al alloy in a dilute aqueous alkaline solution has been shown to be a very powerful reducing agent and is highly effective for the reductive dehalogenation of polyhalogenated phenols and aromatic ring hydrogenation of phenols to the corresponding cyclohexanols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Chlorinated phenols are common aquatic pollutants due to their biocidal properties and solubility in water [5][6][7]10,12,14,15,17,18,20,[26][27][28][29]31]. Due to this reason the possible reductive degradation of several chlorinated phenols was studied via HDC process testing both Devarda's Al-Cu-Zn and Raney Al-Ni alloys.…”
Section: Dechlorination Of Chlorinated Phenolic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chlorinated phenols are common aquatic pollutants due to their biocidal properties and solubility in water [5][6][7]10,12,14,15,17,18,20,[26][27][28][29]31]. Due to this reason the possible reductive degradation of several chlorinated phenols was studied via HDC process testing both Devarda's Al-Cu-Zn and Raney Al-Ni alloys.…”
Section: Dechlorination Of Chlorinated Phenolic Compoundsmentioning
confidence: 99%
“…At least two reaction mechanisms are possible using Al-Ni as the HDC reagent. In most cases, Raney Al-Ni alloy in the alkaline aqueous solution is a much more active HDC agent than the commercial Raney Ni catalyst in co-action of different reductants in the same reaction medium [18][19][20][21][22][23][24][25]28]. As mentioned by Yang et al [28], the Al-Ni alloy is composed of a galvanic couple between the active Al anode and the stable Ni cathode after the dissolution of the Al 2 O 3 protection film by OH -.…”
Section: Possible Pathways Of Raney Al-ni Alloy Hdc Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…This alloy contains 50 wt% of Al and 50 wt% of Ni bound in the form of Al 3 Ni and Al 3 Ni 2 . Different bases such as NaOH or KOH [88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104], alkali metal carbonates [89,94,95], NaF [100] or some alkaline salts of complexing agents [91,101] were proved for HDH processes. It was observed that Raney Al-Ni alloy is, especially in diluted aq.…”
Section: Utilization Of Raney Al-ni Alloy In Hdh Processesmentioning
confidence: 99%
“…It was observed that Raney Al-Ni alloy is, especially in diluted aq. NaOH or KOH, a very effective and universal HDH agent enabling quantitative HDH of Ar-Br, Ar-Cl compounds at elevated temperature [89,90,95,96,99,102,104] or even at room temperature [81][82][83][84][85][86][87][88][89][90][91][92][93][94]98,103].…”
Section: Utilization Of Raney Al-ni Alloy In Hdh Processesmentioning
confidence: 99%